Valores normales de potenciales evocados somatosensoriales del nervio iliohipogástrico en una muestra de adultos sanos (2020)
INTRODUCTION: Pelvic pain of neurogenic origin is characterized by paresthesia in the inguinal or upper pubic region, and includes mechanical damage to the iliohypogastric, ilioinguinal and genitofemoral nerves, within its etiology, during pelvic or gynecological surgery. Electrodiagnostic tests become a very useful tool in diagnosis, whose reference values have not been studied quantitatively in our environment. OBJECTIVE: To present the reference values of the somatosensory evoked potentials of the iliohypogastric nerve, by means of a linear regression analysis, taking into account the anthropometric and electrodiagnostic variables obtained. METHODS: Using a prospective methodology, participants were recruited without suspicion or prior diagnosis of neuropathy or abdominopelvic surgery. For each individual, the somatosensory evoked potential of the iliohypogastric nerve was acquired, recording the latencies P1, N1 and amplitude of the right and left side, and the latencies P37 and N45 of the right posterior tibial nerve. A multiple linear regression model was used with the selected predictors. RESULTS: A P1 latency prediction model was designed with the selected variables. For this model, it was not possible to reject the hypothesis of a slope different from 0 for the variables sex, height, and P37 latency, for which reason another model was created to predict N1 latency with the selected variables. The mean difference N1 minus P1 was then evaluated and a 95% confidence interval was constructed. These values were 9.36ms ± 0.621ms. That is, from the prediction of latency N1, it is possible to estimate latency P1 by subtracting a constant value. CONCLUSION: The establishment of normative values of the somatosensory evoked potentials of the iliohypogastric nerve are useful during the clinical evaluation of patients in whom pelvic pain of neurogenic origin is studied.